1998
DOI: 10.1038/sj.ejcn.1600622
|View full text |Cite
|
Sign up to set email alerts
|

A community based study of vitamin A and vitamin E status of adolescent girls living in the Shire valley, Southern Malawi

Abstract: Objective: To assess vitamin A and E status and anaemia in non-pregnant Malawian adolescent girls. Design: A cross-sectional study in rural village communities in the Shire Valley, Southern Malawi. Subjects: Adolescent girls, n 118, aged between 10 and 19 y, 112 of whom were unmarried. Methods: Socio-demographic information was collected by questionnaire, heights and weights were measured. Vitamin A was assessed by the Modi®ed Relative Dose Response (MRDR) test, in addition to serum retinol values. Blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…There are also factors that may have affected the iron status indicators in the different regions, including the presence of infection (especially malaria) or inflammation [19,20]. The median plasma retinol concentration in our sample was similar to the mean serum concentration found for 10-to 19-year-old Malawian girls [52]. The authors did not, however, report the season of data collection.…”
Section: Low Prevalence Of Deficiencysupporting
confidence: 81%
“…There are also factors that may have affected the iron status indicators in the different regions, including the presence of infection (especially malaria) or inflammation [19,20]. The median plasma retinol concentration in our sample was similar to the mean serum concentration found for 10-to 19-year-old Malawian girls [52]. The authors did not, however, report the season of data collection.…”
Section: Low Prevalence Of Deficiencysupporting
confidence: 81%
“…Babrin and Babrin (1992) reviewed several studies showing that in well-nourished r10-y-old girls, plasma retinol concentrations and retinol binding protein (RBP) were lower than in female adolescents, despite the fact that good liver stores of retinol had been reported in young female subjects. Furthermore, other researchers found that plasma retinol was related to age in female adolescents: the lower the age, the greater the chance of them having concentrations under 0.70 mmol/l, and the menarche reduced the possibility of lower values (Frazio-Tirrozzo et al, 1998). These findings contribute to confirm our results since plasma retinol deficiency was 75% in individuals under 12 y of age.…”
Section: Discussionsupporting
confidence: 89%
“…However, when a relative dose-response test was applied, the percentage of women with retinol deficiency was 76%. In another study, researchers found that 26.6% female adolescents from Malawi had o0.70 mmol/l concentrations of retinol and 40% of them had a relative dose-response test 40.06 (Frazio-Tirrozzo et al, 1998). Based on this lack of correlation between the two different tests used to measure plasma retinol, we proposed that the serum retinol concentrations might not be the best indicator of the nutritional status of vitamin A.…”
Section: Discussionmentioning
confidence: 93%
“…Vitamin E status is influenced by a number of factors (e.g., dietary fat intake, body mass index, smoking, seasonal variation in food availability), and the vitamin E levels found in this study were similar to those reported previously in studies of African females [20,21]. This study was not designed to test the hypothesis that higher vitamin E intake or vitamin E supplementation would influence HIV-1 disease progression.…”
Section: Discussionsupporting
confidence: 84%